A dictionary for the modern flutist - Maclagan, Susan J., 1952-; ebrary, Inc. (Lanham, Md. : Scarecrow Press, 2009)
"A Dictionary for the modern flutist presents clear and concise definitions of more than 1,500 common flute-related terms that a player of the Boehm-system flute may encounter. Fully illustrated with more than 100 images, the entries contain descriptions of words related to all aspects of the flute: flute types, flute parts, flute repair, playing techniques, acoustics, articulations, intonation, common ornaments, flutemaking, flute history, flute music books, and more. Susan Maclagan has thoroughly researched and classified each term, including important flute words that have caused confusion or not been clearly defined previously, listing them alphabetically with concise, in-depth definitions. Carefully labeled illustrations for many flute types, parts, mechanisms, and accessories help to make the definitions easier to visualize. The entries also consist of brief biographies of more than 50 significant names in the flute community worldwide. Several appendixes provide further information on subjects like flute classifications, types of modern Boehm-system flutes and their parts, key and tone hole names, head joint options, and orchestra and opera audition excerpts. Two articles, Checking Your Flute Tuning and Scale by the flutist and pedagogue Trevor Wye - who also contributed the foreword - and Flute Clutches by the historian David Shorey, are also included, as well as an extensive bibliography."--Publisher's description.
The dictionary (p. 1-205) -- Appendix 1, Various flute classifications -- Appendix 2, One-keyed, two-keyed, and simple-system flutes -- Appendix 3, One-keyed, two-keyed, and simple-system flute parts -- Appendix 4, Flute clutches / David Shorey -- Appendix 5, Parts from older or modified Boehm flutes -- Appendix 6, The family of Boehm-system flutes -- Appendix 7, Basic modern flute parts -- Appendix 8, Boehm flute key and tone hole names -- Appendix 9, Common modern flute options -- Appendix 10, Some modern head joint options -- Appendix 11, An easy guide to checking your flute tuning and scale / Trevor Wye -- Appendix 12, Tools of the trade -- Appendix 13, Anatomy of the human head, neck, and mouth -- Appendix 14, Orchestra and opera audition excerpts.
Includes bibliographical references (p. 237-245).
Electronic reproduction.
Keywords: Flute -- Dictionaries; Flute players -- Biography -- Dictionaries; Electronic books